2011
DOI: 10.1007/s00125-011-2408-x
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary time, breaks in sedentary time and metabolic variables in people with newly diagnosed type 2 diabetes

Abstract: Aims/hypothesis We investigated whether objectively measured sedentary time and interruptions in sedentary time are associated with metabolic factors in people with type 2 diabetes. Methods We studied 528 adults (30-80 years) with newly diagnosed type 2 diabetes, who were participants in a diet and physical activity intervention. Waist circumference (WC), fasting HDL-cholesterol, insulin and glucose levels, HOMA of insulin resistance (HOMA-IR) and physical activity (accelerometer) were measured at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
171
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(199 citation statements)
references
References 35 publications
20
171
1
7
Order By: Relevance
“…Consistent with previous results that MVPA showed no or weak independent associations with cardiometabolic biomarkers in individuals with diabetes mellitus,10, 11, 39 our study also did not find significant associations between MVPA and reaching CVD risk factor control goals in US Hispanics/Latinos with diabetes mellitus. This might be due to low levels of MVPA in people with diabetes mellitus 40.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous results that MVPA showed no or weak independent associations with cardiometabolic biomarkers in individuals with diabetes mellitus,10, 11, 39 our study also did not find significant associations between MVPA and reaching CVD risk factor control goals in US Hispanics/Latinos with diabetes mellitus. This might be due to low levels of MVPA in people with diabetes mellitus 40.…”
Section: Discussionsupporting
confidence: 92%
“…However, few studies have investigated these associations using objective physical activity–related measurements in individuals with diabetes mellitus. Previous studies among individuals with newly diagnosed diabetes mellitus found that sedentary time, but not MVPA, was associated with cardiometabolic biomarkers 10, 11. Relationships of sedentary time and physical activity with reaching major CVD risk control goals among individuals with diabetes mellitus remain unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Contrary to our hypothesis, breaks decreased when using the technology as compared with baseline. The number of breaks in sedentary time observed at baseline (83 breaks) are similar to the average number of breaks reported by Cooper et al [34] (84 breaks) among individuals newly diagnosed with type 2 diabetes. The break duration and intensity found at baseline and 1 month were also comparable with those reported in a cross-sectional study conducted by Healy et al [12].…”
Section: Discussionsupporting
confidence: 86%
“…Other studies have however shown favourable associations between accelerometer measured interruptions to sedentary time with WC 8,9,22 and BMI. 8 Healy et al 8 The contrasting evidence between the findings in the present study and those that use accelerometers could be explained by the different methods used to assess an 'interruption'.…”
Section: Discussionmentioning
confidence: 89%
“…9,[21][22][23][24][25][26] For example, British researchers reported that each additional hour of sedentary time is associated with a 1.89cm larger WC in 30 to 80 year olds with newly diagnosed type 2 diabetes. 22 Although accelerometers may not directly measure sitting, these cumulative findings suggest associations between sedentary time and WC and BMI.…”
Section: Discussionmentioning
confidence: 99%